2015
DOI: 10.1007/s11883-015-0507-8
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Receptors in Vascular Biology

Abstract: Nuclear receptors sense a diverse group of steroids and hormones (estrogens, progesterone, androgens, glucocorticoid and mineralocorticoid), vitamins (A and D), lipid metabolites, carbohydrates and xenobiotics. In response to these diverse but critically important mediators, nuclear receptors regulate the homeostatic control of lipids, carbohydrate, cholesterol and xenobiotic drug metabolism, inflammation, cell differentiation and development, including vascular development. The nuclear receptor family is one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…NRs are involved in the control of numerous physiological activities including metabolism ( 86 , 87 ), reproduction ( 88 , 89 ), cell cycle ( 90 ), vasculature ( 91 , 92 ), brain activity ( 93 , 94 ), circadian rhythm ( 95 97 ) and immunity ( 98 103 ). NRs have then been widely implicated in the control of inflammatory processes and the control of immune cell activity ( 99 ).…”
Section: Nuclear Receptorsmentioning
confidence: 99%
“…NRs are involved in the control of numerous physiological activities including metabolism ( 86 , 87 ), reproduction ( 88 , 89 ), cell cycle ( 90 ), vasculature ( 91 , 92 ), brain activity ( 93 , 94 ), circadian rhythm ( 95 97 ) and immunity ( 98 103 ). NRs have then been widely implicated in the control of inflammatory processes and the control of immune cell activity ( 99 ).…”
Section: Nuclear Receptorsmentioning
confidence: 99%
“…49,50 We have previously shown that female sex hormones including17b-estradiol and progesterone inhibit IL-1b-induced collagen degradation by corneal fibroblasts as well as the IL-1b-induced phosphorylation of p38 MAPK, but not that of ERK or JNK, in these cells. 16 In addition, the glucocorticoid receptor agonist dexamethasone inhibits IL1b-induced collagen degradation by corneal fibroblasts as well as the IL-1b-induced phosphorylation of ERK and JNK, but not that of p38 MAPK, in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…PPARβ signalling includes the classical PPAR-RXR pathway to regulate target gene induction and trans-repression of the transcription factor BCL-6 (Lee, et al, 2003) and/or protein kinase PKCα (Ali, Armstrong, et al, 2009;Ali, Hall, Desvergne, Warner, & Mitchell, 2009;Mitchell, et al, 2014). The pharmacological relationship between PGI2 drugs in their interaction with IP versus PPARs is reviewed elsewhere (Belvisi & Mitchell, 2009;Bishop-Bailey, 2015;Mitchell, et al, 2014;. PGI2 drugs include, injectable treprostinil, iloprost, beraprost and newer orally active selexipag (Mitchell, et al, 2014).…”
Section: Pgi2 Drugsmentioning
confidence: 99%